2015
DOI: 10.1038/jid.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Granulation Tissue and Wound Strength in the Absence of α11β1 Integrin

Abstract: Previous wound healing studies have failed to define a role for either α1β1 or α2β1 integrin in fibroblast-mediated wound contraction, suggesting the involvement of another collagen receptor in this process. Our previous work demonstrated that the integrin subunit α11 is highly induced during wound healing both at the mRNA and protein level, prompting us to investigate and dissect the role of the integrin α11β1 during this process. Therefore, we used mice with a global ablation of either α2 or α11 or both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 42 publications
(58 reference statements)
2
83
0
Order By: Relevance
“…The picture of collagen-binding integrins playing a relatively minor role in normal physiology contrasts with the severe phenotypes that have been documented when the ligands of these integrins -members of the collagen family -are defective . Recent data, however, have highlighted the contribution of the collagen-binding integrins to fibroblast function in wounds (Schulz et al, 2015), in fibrotic tissue (TaliorVolodarsky et al, 2015) and tumor models (Lu et al, 2014;Navab et al, 2015). These findings, which establish important roles for collagen-binding integrins in relation to fibroblasts, are timely and fit well into the recent awareness that wound healing, fibrosis and tumor-stroma interactions share key mechanisms at the molecular level (Rybinski et al, 2014).…”
Section: Introductionsupporting
confidence: 61%
“…The picture of collagen-binding integrins playing a relatively minor role in normal physiology contrasts with the severe phenotypes that have been documented when the ligands of these integrins -members of the collagen family -are defective . Recent data, however, have highlighted the contribution of the collagen-binding integrins to fibroblast function in wounds (Schulz et al, 2015), in fibrotic tissue (TaliorVolodarsky et al, 2015) and tumor models (Lu et al, 2014;Navab et al, 2015). These findings, which establish important roles for collagen-binding integrins in relation to fibroblasts, are timely and fit well into the recent awareness that wound healing, fibrosis and tumor-stroma interactions share key mechanisms at the molecular level (Rybinski et al, 2014).…”
Section: Introductionsupporting
confidence: 61%
“…Decreased stiffness and tensile strength were seen in scars from P311 À/À mice compared with scars from WT animals. Reduced scar collagen formation and tensile strength have also been observed in mice lacking a11b1 integrin 41 and in diabetic rats, in which these abnormalities lead to higher incidence of dehiscence. 42 Of interest, reduced collagen deposition is not necessarily coupled with decreased tensile strength, because the opposite has been shown with poly-N-acetyl-glucosamine nanofiber treatment 43 or with the use of a selective adenosine A2AR-antagonist.…”
Section: Discussionmentioning
confidence: 94%
“…Significantly, the hypocollagenization and decrease in scar tensile strength observed in a11b1 integrin-null mice were also linked to defective TGF-b signaling. 41 As part of our in vitro characterization effort, we performed functional studies using MFs and HFs. These showed that P311 stimulated smooth muscle actin production, increased proliferation, promoted migration, and increased contractility of both MFs and HFs, all consistent with induction of the activated state 49 and the transition to myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Wounds were created and harvested according to standard protocols (Blumbach et al, 2010;Schulz et al, 2015;Zweers et al, 2007). In brief, female mice at the age of 10 weeks were anesthetized by intraperitoneal injection of ketamine (10 g/l) and xylazine (8 g/l) solution (10 µl/g body weight) (Park Davis, Karlsruhe, Germany and Erlangen, Germany, respectively).…”
Section: Wound Healing and Fibrosismentioning
confidence: 99%
“…To determine the in vivo relevance of COMP for collagen secretion, COMP-null and control mice were subjected to repeated intradermal injections of bleomycin (Yamamoto et al, 1999) or to excisional wounding (Blumbach et al, 2010;Gurtner et al, 2008;Schulz et al, 2015;Zweers et al, 2007).…”
Section: Comp Facilitates Collagen Secretion In Dermal Fibroblastsmentioning
confidence: 99%